Effectiveness of a Telehomecare Program on Quality of Life of Homebound and Bedridden Elderly and Caregiver Stress in Phakhao Sub-district, Phakhao district, Loei Province - Kannala, Supannee (JOURNAL OF LOEI PROVINCIAL PUBLIC HEALTH OFFICE, 2026)
Thailand is rapidly becoming an aged society, increasing the number of homebound and bedridden older adults, particularly in rural areas with limited access to healthcare, where family caregivers face substantial burden and stress. Telehomecare may improve healthcare access and quality of life while reducing caregiver stress. To compare the effectiveness of a Telehomecare Program on quality of life of homebound and bedridden elderly (WHOQOL-OLD) and caregiver stress (ST-5), and to assess caregiver satisfaction. A quasi-experimental two-group pretest-posttest design enrolled 58 homebound and bedridden elderly (ADL < 11) and 58 caregivers, allocated to intervention (n = 29) and control (n = 29) groups by probability proportional to size sampling. The intervention group received an 8-week Telehomecare Program via the LINE application; the control group received standard care. Data were analyzed using descriptive statistics, paired t-tests, and independent t-tests. After the intervention, overall quality of life among elderly increased from 2.03 ± 0.99 to 3.13 ± 0.31 (t = -10.062, p < .001, d = 1.868) and exceeded the control group (3.13 vs 1.92, t = -23.416, p < .001). Caregiver stress decreased from 3.48 ± 0.63 to 2.54 ± 0.60 (t = 9.639, p < .001, d = -1.790). Social Participation improved most (d = 3.182), followed by Death and Dying (d = 2.350); Sensory Abilities improved least (d = 0.490). Caregiver satisfaction was high (M = 4.302, SD = 0.831). The Telehomecare Program significantly improved quality of life among homebound and bedridden elderly and reduced caregiver stress, supporting its integration into primary and community-based elderly care, particularly in rural settings.